Tourism by utillizing fishery and marine resources are divided within two parts, namely freshwater tourism and marine torism that is a special toursm by doing activities at seascape (under and surface waters) and landscape. One of the potential place to develop marine tourism is Gili Trawangan, Village Gili Indah, District Pemenang, Region Lombok Barat, Provincy Nusa Tenggara Barat. The uniqueness of biodiversity like coral reef and flora-fauna are tourism objects that tourist from domestic and - Gatot Yulianto; Achmad Fahrudin; Nellyana Kusumaningsih (Buletin Ekonomi Perikanan, 2007)
Tourism by utillizing fishery and marine resources are divided within two parts, namely freshwater tourism and marine torism that is a special toursm by doing activities at seascape (under and surface waters) and landscape. One of the potential place to develop marine tourism is Gili Trawangan, Village Gili Indah, District Pemenang, Region Lombok Barat, Provincy Nusa Tenggara Barat. The uniqueness of biodiversity like coral reef and flora-fauna are tourism objects that tourist from domestic and foreign are interested. This study are aimed to analyze demand toursm, analyze consumer's surplus and establish some strategy for developing marine toursm at Gili Trawangan. The sampling method for this study are purposive sampling based on tourism activities of tourst and the toursts have jobs. Based on the result of study are known that parts of tourism industry are toursm atraction, toursm services and toursm transportation. Function of demand toursm are Ln Q = -0,773 -0,068Ln Xl + 0,051Ln X 2 +0,773Ln X3 ~ 0,358D Demand elasticity are -0,0068 that is the demand fungtion are elastic. Consumer's surplus at the Gili Trawangan at 2006 are US$ 8.724.613,25 per year. Strategy for developing marine toursm at Gili Trawangan are (a) Creating the tourism image to increase level visting, (b) Creating communication and patnership within managing resources (c) Establishing tourism perception by using natural resources and facility in order to positive impacs for community.